Predictive capacity of prodromal symptoms in first‐episode psychosis of recent onset. Issue 3 (8th November 2017) - Barajas, Ana; Pelaez, Trinidad; González, Olga; Usall, Judith; Iniesta, Raquel; Arteaga, Maria; Jackson, Chris; Baños, Iris; Sánchez, Bernardo; Dolz, Montserrat; Obiols, Jordi E.; Haro, Josep M.; et al.
Abstract : Background: Both the nature and number of a wide range of prodromal symptoms have been related to the severity and type of psychopathology in the psychotic phase. However, at present there is an incomplete picture focused mainly on the positive pre‐psychotic dimension. Aim: To characterize the prodromal phase retrospectively, examining the number and nature of prodromal symptoms as well as their relationship with psychopathology at the onset of first‐episode psychosis. Methods: Retrospective study of 79 patients experiencing a first‐episode psychosis of less than 1 year from the onset of full‐blown psychosis. All patients were evaluated with a comprehensive battery of instruments including socio‐demographic and clinical questionnaire, IRAOS interview, PANSS, stressful life events scale (PERI) and WAIS/WISC (vocabulary subtest). Bivariate associations and multiple regression analysis were performed. Results: Regression models revealed that several prodromal dimensions of IRAOS (delusions, affect, language, behaviour and non‐hallucinatory disturbances of perception) predicted the onset of psychosis, with positive (22.4% of the variance) and disorganized (25.6% of the variance) dimensions being the most widely explained. Conclusion: In addition to attenuated positive symptoms, other symptoms such as affective, behavioural and language disturbances should also be considered in the definitions criteria of at‐high‐risk people.